Pemahaman Relasional Siswa pada Turunan Fungsi dengan Bantuan Software Geometer’s Sketchpad - Cut Laila Kulsum; Rahmah Johar; Said Munzir (Universitas Syiah Kuala, 2019)
Relational understanding in mathematics is important for the student's it causes understanding the mathematical concepts will be memorable if he knows the process of getting the concept by linking it with the knowledge to be learned. This study aimed to examine the relational understanding of students in discovering the concept of f '(x) using Geometer's Sketchpad, and the relational understanding of students in discovering the concept of f (x) = x2 + c let f' (x) = 2x using Geometer's Sketchpad. It also investigated the students' responses when they use Geometer's Sketchpad in understanding the derivative function. The study used a qualitative approach. Subjects in this study were three Year 11 students of one the junior high school in Meuredu, Aceh, Indonesia. The instruments were observation sheet, interview guides, student worksheets and test questions. The data analysis included the classification of information obtained from observations when the subjects used software Sketchpad Geometers in their learning. Information about students' relational understanding obtained from the student worksheets reinforced with test questions and interviews so that the results can be accounted for. This study concluded that (1) students' relational understanding (Subjects RV, subject MR, subject AA) in discovering the concept of f '(x) using Geometer's Sketchpad was good; (2) students' relational understanding (Subjects RV, subject MR, subject AA) in discovering the concept of f (x) = x2 + c let f '(x) = 2x using Geometer's Sketchpad was a good; and (3) the responses of Subjects RV, subject MR, subject AA in using Geometer's Sketchpad were positive, each research subject was very pleased and liked to use Geometer's Sketchpad in understanding the derivative function.